Do anxiety, anger and aggression differentiate elite water-polo players? - Bebetsos, E.; Zouboulias, S.; Antoniou, P.; Kourtesis, T. (Journal of Physical Education and Sport, 2013)
The aim of the study was to investigate if anxiety, anger and aggression differentiate a sample of elite water-polo players, in Greece. The sample consisted of 200 (100 men, 100 women) water-polo players, between the ages of 17-38 years of age. They completed the Greek versions of the CSAI-2 (Stavrou, Zervas, Kakkos, & Psichountaki, 1998), and of the CAAS (Bebetsos, Christoforidis, & Mantis, 2008), instruments. Analyses revealed differences between both sexes and age groups. Younger athletes had higher anxiety, and lower confidence scores, and also women indicated lower anger and aggressive scores. Overall, results shine some light on aspects that effect athletic performance of elite water-polo players in Greece.